The Effect Of Green Marketing Mix On Purchase Intention Of Ecoprint Fashion With Environmental Awareness As A Mediating Variable In Generation Z On Social Media - Dwi Gema Soegesti; Diana Sari; Yevis Marty Oesman (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
This research aims to examine the influence of the Green Marketing Mix on Purchase Intention for ecoprint fashion with Environmental Awareness as a Mediating Variable in Generation Z on Instagram Social Media, with a sample size in this study of 200 Gen Z respondents on Instagram social media. Data collection in this research was done by distributing questionnaires. This analysis technique uses the Structure Equation Model (SEM-PLS) using the SmartPLS 3.0 program with outer modelmeasurements: convergent validity, discriminant validity, reliability test, and inner model measurements; Coeficient Determinant of (R2), Significance (tvalue). The results of this research show that green marketing mix has a significant effect on purchase intention, green marketing mix has a significant effect on environmental awareness, environmental awareness has a significant effect on purchase intention and there is an indirect effect between the green marketing mix variables on purchase intention through environmental awareness.